A personalised user preference and feature based semantic information retrieval system in semantic web search. (2018) - John, Princess Maria; Arockiasamy, S.; Thangiah, P. Ranjith Jeba
In this work, an ontology based Semantic Supported Information Retrieval System (SIRS) is introduced, in which the users give the input query which is determined by the Hypertext Markup Language (HTML) Parser then Probabilistic Latent Semantic Indexing (PLSI) algorithm is utilised to gathered the details in an effective manner. These conversations are preceded, along with the assistance of the field concept of the pre-existing domain ontologies, a mediator thesaurus and determine semantic association amongst them in nature. The proposed work concentrates on resolving the web search issues and also concentrates on resolving the personalised web search. So the SIRS will be correlated to the personalised search with item features, termed as Personalised User Preference and Feature based Semantic Information Retrieval System (PUFSIRS) architecture. PUFSIRS performs according to the particle agent, which accomplishes the SIRS based on the curiosity of the user through Multi-Criteria Particle Swarm Optimisation (MCPSO) for giving user's personal interest. The appropriate details for the semantic query are gathered and categorised based on the pertinence of an MCPSO procedure. The results show that the proposed PUFSIRS architecture can enhance the accuracy and efficiency for gathering the appropriate web-records which are collected from various fields such as food, education, news and healthcare to the current schemes. The result of the proposed PUFSIRS architecture is measured in terms of precision, recall, F-measure, accuracy and processing time.